The Profile of Students’ Questions Based on Revised Bloom’s Taxonomy on Life Organizations System Topic - Nur Eka Kusuma Hindrasti; Hamzah Yuliandie; Trisna Amelia (Bioeducation Journal, 2020)
The aim of this study to determine student questions based on Revised Bloom's Taxonomy. This study was done by quantitative approach with descriptive research method. Research data were obtained through analysis of student questions sheets and interviews. Guide the student’s question were analysid sheet was used to record student questions while learning in class. Based on the results of the analysis it is known that 20% of students' questions at the cognitive domain level C1 (Remembering), 37% at the C2 level (Understanding), 20% at the C3 level (Applying), 11,5% at the C4 level (Analyzing), 11,5% at the C5 level (Evaluating), and 0% at the C6 level (Creating). While based on the dimension of knowledge, factual level questions were asked by 26% of students, conceptual level questions by 74%, and there was no question in procedural and metacognitive level.